2022
DOI: 10.1155/2022/4696415
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D3 Supplementation Attenuates Surgery-Induced Neuroinflammation and Cognitive Impairment by Regulating NLRP3 Inflammasome in Mice

Abstract: Neuroinflammation plays a dominant role in the progression of postoperative cognitive dysfunction (POCD). Vitamin D has been known to have important regulatory functions in inflammation and immune response. The NOD-like receptor protein 3 (NLRP3) is an essential inflammasome in the inflammatory response and could be activated by anesthesia and surgery. In this study, male C57BL/6 mice aged 14–16 months were given VD3 for 14 days straight before having an open tibial fracture surgery. The animals were either sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Animal models have shown that treatment with 1,25(OH)2 D3 inactivates the NLRP3 inflammasome; in consequence, treatment with the hormonally active metabolite of VDES decreased surgeryinduced neuroinflammation and memory and cognitive dysfunctions in aged mice (95). Treatment with 1,25(OH)2 D3 also exerted protective effects against retinal vascular damage and cell apoptosis especially in mice with type 1 diabetes (96).…”
mentioning
confidence: 99%
“…Animal models have shown that treatment with 1,25(OH)2 D3 inactivates the NLRP3 inflammasome; in consequence, treatment with the hormonally active metabolite of VDES decreased surgeryinduced neuroinflammation and memory and cognitive dysfunctions in aged mice (95). Treatment with 1,25(OH)2 D3 also exerted protective effects against retinal vascular damage and cell apoptosis especially in mice with type 1 diabetes (96).…”
mentioning
confidence: 99%
“…Dong et al (2021) found that Vitamin D3 improved nitrogen-induced cutaneous inflammation by deactivating the NLRP3 inflammasome. 26,27 Another study conducted by Ghorbani et al (2020) assessed the effects of supplementation with vitamin D3 on headache characteristics and pro-/anti-inflammatory markers in patients with migraine, taking into consideration the anti-inflammatory effects of this vitamin. 11 The results of the study indicated that the group of patients receiving vitamin D3 supplementation experienced a decrease in the duration of attacks, fewer headache days per month, lower headache severity, and lower monthly consumption of pain relief medication compared to the placebo group.…”
Section: Nlrp3mentioning
confidence: 99%
“…Therefore, the administration of vitamin D3 can reduce NLRP3 levels and inhibit neuroinflammation. 27…”
Section: Nlrp3mentioning
confidence: 99%